Relationship Between Self-Acceptance and Intention to Stay at Work Among Clinical Nurses in China: A Cross-Sectional Online Survey - Kong, Lingling; Qin, Fangxia; Zhou, Aiying; Ding, Shanju; Qu, Hua (Frontiers in Psychiatry, 2022)
Background: During the pandemic and with the growing shortage of nurses, the problem of how to retain existing nurses was of paramount importance. However, there is limited evidence on the relationship between nurses’ self-acceptance and intention to stay. Objectives: This study aimed to investigate the factors influencing nurses’ intention to stay at work, and explore the relationship between self-acceptance and their intention to stay. Methods: Convenience sampling was conducted to select nurses who worked in a clinical environment during June 2020, in hospitals in Shandong Province, China. Self-designed basic information and two questionnaires, namely, the “self-acceptance questionnaire” and “intention to stay” were adopted. Mean, median, related analysis, and regression analysis were adopted to describe the relationship of self-acceptance and intention to stay on part of Chinese nurses. Results: A total of 1,015 clinical nurses participated in the survey. The mean score of intention to stay among participants was 22.00. The multiple regression analysis revealed various factors, such as age, family support the work, interest in work, job suitability, type of employment, professional level, weekly working hours, working department and self-acceptance influenced the nurse’s intention to stay (β range from -1.506 to 2.249). Conclusion: Our findings identified several factors that are significantly related to and impact the level of intention to stay among clinical nurses.